PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN CAT MEREK MOWILEK DI JAKARTA - Lim Yosep (Universitas Mercu Buana, 2013)
Abstract: This study aimed to determine the effect of price perception on purchase decisions and promotion of Mowilex paint,Exogenous variables were examined in this study is the perception of price and promotion variables. While purchasing decisions to be endogenous variables. Primary data were collected through questionnaires daan using purposive sampling with a total sample of 200 customers of PT Mowilex Indonesia in Jakarta. Aplying regression analysis,data are calculated processing to knowperceptual variables affect the price and promotion variables purchasing decisions. The conclusion of this study, all the independen or exogenous variabel influenced to purchasing decisions. So the result make recommendation for companies should focus on mainly on price perception dimension of cost perception and should focus on promotion, especially in the dimension of sales promotion.Keywords: perceptions of price, promotion and purchasing decisions.